Linguopolitical Personology (Metaphorical Perspective of Research) - O. N. Kondratyeva; V. A. Kameneva (Научный диалог, 2020)
The article was accomplished at the intersection of such relevant areas of modern linguistics as political linguistics, linguistic personology and linguistic metaphorology. The purpose of the article is to provide an overview of the work of foreign and domestic linguists for 2009-2019, devoted to the analysis of metaphorical models in the idiolics of politicians, to identify the main trends in research of this kind. The analysis showed that linguistic-personal research on metaphorics in political communication is carried out in a cognitive, pragmatic, stylistic, rhetorical, semiotic, psycholinguistic perspectives. It was revealed that according to the criterion “object of analysis” they can be characterized in territorial, status, ideological, gender, chronological, temporal and comparative aspects. The analytical review presented in the article demonstrates that there is a research asymmetry in modern linguistic-political personology: the work on federal politicians predominates over the work on regional politicians, the work on representatives of the political elite over the work on political opposition, the work on male politicians over the work on politicians - women, work on existing politicians - on work on the great politicians of the past. The authors believe that due to the indicated asymmetry in the objects of research, the task of linguopolitical personology should be to fill in the existing gaps.